EMDR and the Treatment of Medically Unexplained Symptoms: A Case Study. (19th November 2015) - Proudlock, Simon
This current research used a single case study design to examine how Eye Movement Desensitization and Reprocessing (EMDR) was effective for one individual experiencing medically unexplained chronic pain in his abdomen. EMDR is briefly explained as is how it has been adapted to be used with pain. A brief literature review is also included.